Palliedaphichnium gondwanicum new ichnogenus new ichnospecies, a millipede trace fossil from paleosols of the upper Permian Gondwana sequence of India. (September 2021) - Agnihotri, Deepa; Genise, Jorge F.; Saxena, Anju; Srivastava, A.K.
Abstract: The new invertebrate trace fossil from paleosols of the Bijori Formation, Palliedaphichnium gondwanicum new ichnogenus new ichnospecies, which belongs to an upper Permian Gondwana sequence of India, makes a significant contribution to the meager records of invertebrate trace fossils from Permian and Indian paleosols. This trace fossil attributed to Diplopoda and composed of tunnels and chambers filled with pellets is also an important addition to the scarce record of Permian millipedes. The abundance of plant remains in the same paleosol indicates that these millipedes probably fed on leaf litter as other fossil and extant representatives. Chambers and abundant pellets in burrows indicate adverse conditions on the surface, at least seasonally. This finding contributes to the emerging scenario of invertebrate ichnofaunas from paleosols and points to a successive dominance of millipedes during the Paleozoic, crayfishes and earthworms in the Mesozoic, and insects in the Cenozoic. UUID: http://zoobank.org/4378c739-9bd1-4382-b084-e2176045e209